The Scarlet pimpernel (Digiview Productions, 2004)
Leslie Howard, as the dashing superhero who rescues innocent victims of the French Revolution by night, and assumes the identity of Sir Percy Blakeney, a foppish British aristocrat, by day. Co-starring as his wife is the beguiling Merle Oberon, whom Sir Percy still finds time to romance in between his heroic night-time adventures.